High performance dual-electrolyte magnesium–iodine batteries that can harmlessly resorb in the environment or in the body. Issue 10 (7th September 2022) - Huang, Ivy; Zhang, Yamin; Arafa, Hany M.; Li, Shupeng; Vazquez-Guardado, Abraham; Ouyang, Wei; Liu, Fei; Madhvapathy, Surabhi; Song, Joseph Woojin; Tzavelis, Andreas; Trueb, Jacob; Choi, Yeonsik; et al.
Abstract : High-performance eco- and bio-resorbable magnesium–iodine batteries with >1.8 V output power cardiac pacemakers, wireless environmental monitors, thermal sensors, microcontrollers, and Bluetooth systems. Abstract : Batteries represent the dominant means for storing electrical energy, but many battery chemistries create waste streams that are difficult to manage, and most possess toxic components that limit their use in biomedical applications. Batteries constructed from materials capable of complete, harmless resorption into the environment or into living organisms after a desired period of operation bypass these disadvantages. However, previously reported eco/bioresorbable batteries offer low operating voltages and modest energy densities. Here, we introduce a magnesium–iodine chemistry and dual (ionic liquid/aqueous) electrolyte to overcome these limitations, enabling significant improvements in voltage, areal capacity, areal energy, areal power, volumetric energy, and volumetric power densities over any alternative. Systematic studies reveal key materials and design considerations. Demonstrations of this technology include power supplies for cardiac pacemakers, wireless environmental monitors, and thermal sensors/actuators. These results suggest strong potential for applications where commercial battery alternatives pose risks to the environment or the human body.